Influence of play-based learning on socio-emotional development among early childhood children in Afijio Local Government Area of Oyo State, Nigeria - Adubuola, Elizabeth Olaoluwa; Gbadeyanka, Taofeek Akolade; Hamzat, Baniyaminu Opeyemi; Oyewumi, Nasimot Opeyemi (Jurnal Inovasi Teknologi Pendidikan, 2023)
With two key objectives, this study delves into the impact of play-based learning programs on the socio-emotional development of early childhood children in Afijio Local Government Area, Oyo State, Nigeria. Firstly, it examines whether these programs affect socio-emotional development differently based on gender. Secondly, it investigates how school type, whether private or public, influences the effectiveness of play-based learning on socio-emotional development within this region. This study employs a non-randomized quasi-experimental design. The study engaged 132 early childhood children aged 3-5 years from two schools in the area. An Emotional Regulatory Skill Test (ERST) was designed and demonstrated strong reliability (α = 0.84) and content validity. Results revealed that play-based learning programs are intentionally designed for gender-neutral effectiveness, promoting inclusivity and equality. A significant effect of play-based learning programs on socio-emotional development based on school type was found, with private schools providing enriched environments and public schools leveraging diversity for growth. These findings underscore the transformative potential of play-based learning in fostering inclusive socio-emotional development among early childhood children, advocating for gender-equitable programs, and suggesting allocating additional resources to public schools for enriched play-based experiences. Ultimately, the study offers a vision of a harmonious future where socio-emotional development knows no gender boundaries, and every child thrives, regardless of school type.